Sistem Informasi Pencatatan dan Pelaporan Keuangan Berbasis Website di GKS Makamenggit Kabupaten Sumba Timur - Septian Justino Manung Reku Landu Wulang; Arini Aha Pekuwali; Desy Asnath Sitaniapessy (Asosiasi Profesi Telekomunikasi dan Informatika Indonesia, 2024)
The Sumba Christian Church (GKS) Jemaat Makamenggit, located in East Sumba Regency, has a substantial number of congregants, including 425 members at the central Makamenggit church. Financial management activities, such as revenue from Children's Offerings (PA), Diakonia, and building funds, are still carried using notebooks and calculators. This method is not only time-consuming and also prone to recording errors and reduces transparency in financial reporting. This poses challenges in meeting regulatory requirements and maintaining the trust of the congregation and related stakeholders. In the current digital era, transparency and accuracy in financial reporting are essential needs. To address this challenge, a web-based information system which aims to speed up the process of calculating incoming and outgoing money and financial reporting. With this new system, the recording process, which typically takes 1-2 days, can be simplified to just 10-15 minutes. The use of a web-based system also provides real-time access to financial data for various stakeholders, such as church administrators, congregation councils, and supervisory bodies, regardless of geographical constraints. The proposed system will enable the church treasurer to manage church finances more efficiently, reduce reporting time, and meet applicable regulatory demands.In an effort to speed up the financial calculation process at GKS Makamenggit, this financial information system was developed using the waterfall method. It is hoped that the results of this research will help financial treasurers to manage incoming and outgoing finances and with this system, financial reporting will be more transparent and efficient.